Implementasi Strategi Komunikasi Pemasaran dalam Membangun Brand Image UMKM Naza Makeup di Kota Bogor - M. Nabil Zidni; Viro Dharma Saputra (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This research is motivated by the importance of marketing communication strategies for micro, small, and medium enterprises (MSMEs) in building brand image amid the increasingly competitive beauty industry. MSMEs are required to optimize various communication channels effectively to remain competitive and attract consumers. The purpose of this study is to analyze the implementation of marketing communication strategies carried out by Naza Makeup, an MSME in Bogor City, and to evaluate their effectiveness in strengthening brand image. This study employs a qualitative approach using a literature review method, in which data were obtained through an exploration of scientific journals, books, and other relevant academic sources published within the last five years. The findings show that Naza Makeup has attempted to utilize social media, particularly Instagram, as its primary promotional tool, while also relying on word-of-mouth to expand its consumer reach. However, the implementation of these marketing communication strategies has not been fully integrated with the principles of integrated marketing communications. Gaps between theory and practice remain evident, especially in terms of message consistency, market research, and strategic collaboration. These shortcomings limit the effectiveness of communication in strengthening brand image. The results emphasize the need for a more structured, sustainable, and data-driven communication strategy to build a strong and competitive brand image. Furthermore, developing collaborations with influencers, communities, and other industry players is strongly recommended to enhance competitiveness. Therefore, this study provides practical contributions for MSMEs, particularly in the beauty sector, in designing effective marketing communication strategies that support long-term sustainability.